2021
DOI: 10.5005/jp-journals-10005-2006
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Dental Health in Children: A Review of Literature

Abstract: Aim and objective To illustrate the most important general findings significant for dentists dealing with pediatric diabetic patients, as well as the effect of type 1 diabetes mellitus (T1DM) on children's oral health. Background Type 1 DM is considered to be the most popular type of diabetes in children and adolescents which has a strong impact on their lifestyle. Diabetes mellitus (DM) mainly affect organs and tissues that are affluent with blood vessels including kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
2
0
1
Order By: Relevance
“…We hypothesized that the reason was that manual skills were not developed well enough in children of primary school age. This approves the opinion of some authors, who note that the oral hygiene indices did not have significant differences between patients with type 1 DM and the control group [2,3,8]. However, it disproves the opinion of other authors, who found that the value of oral hygiene indices in patients with type 1 DM was much higher compared to healthy patients [16,17,20].…”
supporting
confidence: 79%
See 1 more Smart Citation
“…We hypothesized that the reason was that manual skills were not developed well enough in children of primary school age. This approves the opinion of some authors, who note that the oral hygiene indices did not have significant differences between patients with type 1 DM and the control group [2,3,8]. However, it disproves the opinion of other authors, who found that the value of oral hygiene indices in patients with type 1 DM was much higher compared to healthy patients [16,17,20].…”
supporting
confidence: 79%
“…Type 1 diabetes mellitus is an autoimmune disease in individuals who have a genetic predisposition to it, which leads to the destruction of β-cells of the pancreas with the subsequent development of absolute insulin deficiency. Type 1 diabetes mellitus (DM) is characterized by an increase in the concentration of glucose in the blood due to a deficiency of insulin [1,2,3].…”
mentioning
confidence: 99%
“…However, relatively few data are available for type 1 diabetes mellitus (T1DM) ( 16 ). Studies have found that children with T1DM with age younger than 11.5 years had teeth eruption acceleration, while children older than 11.5 years had delayed teeth eruption process ( 17 ). Type 1 T1DM is becoming more prevalent among young individuals worldwide who is also the main population needing orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Предполагается, что потеря функциональной массы β-клеток происходит по цепочке событий, аналогичной «помощи при самоубийстве» [8], где гибель β-клеток, вероятно, связана с активацией иммунной системы, которая, в свою очередь, и разрушает их. По сути, СД 1-го типа является хроническим аутоиммунным заболеванием [4,5,9]. Аутоиммунный процесс против β-клеток, запускается как триггерами окружающей среды: экологические факторы, инфекции, воздействие определенных токсинов (например, нитраты) [10], так и генетической предрасположенностью [2,4,6].…”
Section: Introductionunclassified